2018
DOI: 10.1021/acs.jafc.8b03049
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Quercetin from Onion Extracts after Intraruminal Application in Cows

Abstract: The aim of the present study was to investigate the bioavailability of quercetin from onion bulb (OB) and onion skin (OS) extracts in ruminants. Three non-lactating cows equipped with a permanent rumen fistula intraruminally received equimolar amounts of quercetin as either aglycone, rutin, or OB or OS extract, respectively, at a dose of 50 mg of quercetin equivalents/kg of body weight. Blood samples were drawn before and frequently within the 24 h period after application of the respective substance. Querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Several flavonoid metabolites were detected in human plasma, including tamarixetin, isorhamnetin, and kaempferol; however, their quantity is much lower than quercetin in plasma. In plasma, the major circulating metabolites of Q are conjugated with glucuronide, methyl, or sulfates, such as quercetin 3- O -β-D-glucuronide (Q3GA) and quercetin-3’-sulfate [ 44 ]. Thus, physiologically speaking, these phase-II metabolites, instead of R/Q, enter into the circulation system and exert their biological functions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several flavonoid metabolites were detected in human plasma, including tamarixetin, isorhamnetin, and kaempferol; however, their quantity is much lower than quercetin in plasma. In plasma, the major circulating metabolites of Q are conjugated with glucuronide, methyl, or sulfates, such as quercetin 3- O -β-D-glucuronide (Q3GA) and quercetin-3’-sulfate [ 44 ]. Thus, physiologically speaking, these phase-II metabolites, instead of R/Q, enter into the circulation system and exert their biological functions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of relative bioavailability includes a comparison of two formulations or two routes of administration of the same formulation without involving intravenous administration. However, studies examining the relative bioavailability of flavonoids in general are more common [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Bioavailability and Metabolism Of Quementioning
confidence: 99%
“…Studies have shown that ruminal microbes can break the b-glycosidic bond of rutin (quercetin3-O-rutinoside) leading to the release of quercetin and effectively enhancing its bioavailability in the gastrointestinal tract [125]. Furthermore, quercetin along with its methylated (isorhamnetin, tamarixetin) and dehydroxylated (kaempferol) derivatives have been detected in the systemic circulation of non-lactating cows [126], indicating a role of rumen microbes in flavonoid metabolism (Figure 3). Studies on the bioavailability of quercetin in ruminants are limited [96,125]; however, extensive reports are available in monogastric animals [7,127,128].…”
Section: Ruminal Degradation Absorption and Bioavailability Of Mulber...mentioning
confidence: 99%
“…Animals 2020, 10, x 8 of 24 along with its methylated (isorhamnetin, tamarixetin) and dehydroxylated (kaempferol) derivatives have been detected in the systemic circulation of non-lactating cows [126], indicating a role of rumen microbes in flavonoid metabolism (Figure 3). Studies on the bioavailability of quercetin in ruminants are limited [96,125]; however, extensive reports are available in monogastric animals [7,127,128].…”
Section: Ruminal Degradation Absorption and Bioavailability Of Mulber...mentioning
confidence: 99%